Participatory tomato variety selection in the lowland areas of North Shewa - Natnael Girma; Abdu Yassin; Zerihun Kebede; Getaneh Geto; Tigist Firew; Fiseha Desalegne; Alemayehu Ayele; Damtew Aragaw; Dejene Mamo; Teklemariam Ayele (Journal of Oasis Agriculture and Sustainable Development, 2023)
The production and productivity of tomatoes in Ethiopia as well as in Amhara Region are very low because of lack of improved and adapted varieties, inadequate knowledge of production and management, and a poor marketing system. The field experiment was carried out during the 2018 irrigation seasons at Ataye and Shewarobit to identify adaptive, high yielding and disease tolerant varieties of tomato. Eight improved tomato varieties were laid out in a randomized complete block design and replicated three times. The collected biological data were analyzed using SAS statistical software version 9.4, and farmers’ preferences for those varieties were also assessed based on selection attributes set by them. The combined analysis of variance revealed that there was significant difference between the varieties on the number of fruits per cluster, plant height, marketable number, unmarketable number and average weight of a tomato. The highest number of fruits per cluster was recorded from variety Mersa (3.83), followed by Melkasalsa (3.73) and Melkashola (3.7). The variety Mersa was the tallest followed by Weyno with plant heights of 110.5 cm and 110.96 cm, respectively.  The highest average fruit weight was recorded for the variety D2 (61.25 g) followed by Cochoro (46.46 g). Even though it was not statistically significant, the variety Melkashola has given the highest marketable yield (32.98 t ha-1) and showed a better reaction to late blight disease as low as 27.5 %. In addition to this, variety Melkashola was highly preferred by the farmers. Based on the biological data and farmer’s preference variety Melkashola has been recommended for Ataye and Shewarobit as well as for other similar agro-ecologies.